ECONOMIC FOUNDATIONS OF THE ANGLO-SAXON ALLIANCE’S CONSOLIDATION AS A DOMINATING ELEMENT OF THE GLOBAL SOCIAL SYSTEM - Alexey N. Yeletsky (Статистика и экономика)
The various aspects of economic interactions of the key Anglo-Saxon states are considered in the article. Commercial, ﬁnancial, technological fundamentals ofthe collaboration and interdependenceof Anglo-Saxon countries are analyzed. The signiﬁ cant role of the USA and Great Britain as leading centers of this leadingblock is emphasized. The particular attention is paid to the aspiration of the Anglo-Saxon alliance retain geo-economic andgeopolitical leadership under conditionsof strengthening trends of multipolarity